Voice - Alanna McArdle (Janeway JS, 2020)
Voice is an extract from a longer text that comprises five parts of poetry, lyric essays, and prose-poetry. The text uses the lyric ‘I’ and considers the radical possibilities of its application in the interrogation of trauma and selfhood, and the conflict between self-definition and medical/institutional definition. Voice blurs and interrogates the generic and formal distinctions of poetry and life writing to pose questions of how writer and speaker interconnect, and to explode arbitrary literary conventions which themselves limit and oppress in their rigidity of definition. Voice is both narrative and lyrical, tracking part of my experience as a person with Bipolar Disorder inside and outside of medical institutions. The text explores the possibility of recalibrating or reclaiming the oppressive syntax of medicine, and asks how the self is transformed through not just the experience of illness, but also illness’s subsequent side effect of institutionalisation, and the intersections of other “othered” and marginalised identities and experiences within this discursive categorisation. Voice draws on and re-appropriates the derisive and misogynistic label of “confessional writing” and confronts the historical nexus of discriminations that has led to what psychiatrist and author Phyllis Chesler calls “the female career as psychiatric patient.”
Keywords: poetry; activism; history; subjectivity